Ceria-coated replicated aluminium sponges as catalysts for the CO-water gas shift process. (26th March 2021) - Palma, Vincenzo; Goodall, Russell; Thompson, Adam; Ruocco, Concetta; Renda, Simona; Leach, Richard; Martino, Marco
Abstract: A study on the use of chemical conversion coating as a preparative technique for foam-based structured catalysts, in the water gas shift reaction, is presented. The results showed a significant correlation between the textural properties of the structure and the preparation technique, highlighting how chemical conversion coating is a suitable technique for highly porous structures. In the first part of the paper, the performance of two structured catalysts obtained by coating commercial aluminium foams, with different porosity, was compared. The activity tests suggested that diffusion phenomena occurred in the case of the uncompressed foams. These results were confirmed by evaluating the performance of a catalyst obtained by coating a compressed 5 PPI pore size commercial aluminium foam, which showed much higher activity, at the same contact time, with respect to the catalyst obtained with the corresponding non-compressed foam. Finally, the performance of a catalyst obtained by coating an aluminium sponge, synthesized by the replication technique, was compared to that of a catalyst obtained by coating a compressed 40 PPI pore size aluminium foam. The higher activity of the sponge-based catalysts confirmed the dependence of the activity on the textural properties of the structure: X-ray computed tomography images highlighted the narrow distribution of the pore sizes and the presence of "bottleneck type" connections in the sponge structure, which are beneficial for the activity of the catalyst. Graphical abstract: Image 1 Highlights: Chemical conversion coating can be used in structured catalysts preparation. The best coating technique depends on the textural properties of the structure. The "bottleneck type" connections in replicated sponge favour the activity.